Boston Violence Intervention Advocacy Program: A Qualitative Study of Client Experiences and Perceived Effect. (16th July 2014) - James, Thea L.; Bibi, Salma; Langlois, Breanne K.; Dugan, Elizabeth; Mitchell, Patricia M.; Mello, Michael J.
Abstract Objectives This study intended to explore clients' experiences and provide a contextual basis for understanding their perceptions of the effectiveness of the Boston Medical Center (BMC) Violence Intervention Advocacy Program (VIAP). Methods This was an exploratory, qualitative study conducted in an urban, Level I trauma center from July 1, 2011 to February 24, 2012. Emergency department (ED) patients older than 18 years with penetrating trauma, and who were enrolled in the VIAP, were eligible. Two trained, qualitative interviewers who were not part of the VIAP obtained consent and conducted in‐depth, semistructured interviews. Interviews were audiotaped, transcribed, deidentified, coded, and analyzed. Thematic content analysis consistent with grounded theory was used to identify themes related to client experiences with VIAP, life circumstances, challenges to physical and emotional healing postinjury, services provided by VIAP, and perceptions of VIAP's effectiveness. Results Twenty subjects were interviewed. Most were male, African American, and younger than 30 years of age, reflecting the overall program's clientele. Most subjects perceived their advocates as caring adults in their lives and cited aspects of the peer support model that helped establish trusting relationships. Major challenges to healing were fear and safety, trust, isolation as a coping mechanism, bitterness, and symptoms of posttraumatic stress disorder (PTSD). Every subject noted important services provided by VIAP advocates. Most subjects explicitly stated that they had positive experiences with the VIAP and perceived advocates' roles as a positive influence, providing client‐centered advocacy, education, and support. Conclusions This study provides insight into the lives of 20 BMC VIAP clients and contextualizes their unique challenges. Participants described positive, life‐changing behaviors on their journey to healing through connections to caring, supportive adults. Information gained from this study will help the VIAP to further support its clients. However, future research is needed to identify best practices for ED‐based violence intervention programs and to measure community‐wide efficacy in different settings.